HUMAN CAPITAL AS A RESOURCE FOR THE SOCIAL AND ECONOMIC DEVELOPMENT OF UKRAINE - Nataliia Vasіutkina; Oksana Kondratiuk; Iryna Stoianenk; Samira Piletska (Academy Review, 2025)
The article examines the key trends and challenges of human capital as the primary lever of Ukraine’s socio-economic development. The socio-economic essence and components involved in the formation and development of human capital, such as standard of living, education, and material well- being, are analyzed. Using a composite approach, the key human development indicators that underlie the formation, accumulation, and growth of the country’s human capital have been studied. It was established that a relationship exists between the level of human capital development and the country’s overall economic and social progress. The main determinants exerting the greatest influence on the formation and effective use of human capital in Ukraine are identified. With the use of structural and dynamic analysis, an assessment of the development of human capital for the period 2012-2022 was carried out. The problems of human capital in the economic dimension are analyzed through a number of economic factors: gross domestic product, income and expenditure of the population, unemployment, inflation, and wages. Correlation-regression analysis between the determined factors demonstrated the existence of a close relationship between the incomes of the population, gross domestic product, and wages. This gave the authors reason to claim that the growth of gross domestic product and wages contributes to an increase in the income of the population, which, in turn, has a positive effect on the potential opportunities for the qualitative development of human capital. The problems of the social dimension are analyzed through a number of social factors: the demographic situation, the education of the population, the quality of health care, the state of the environment, and the social policy of the state. The authors proved that the process of formation and development of human capital in Ukraine today can be considered more negative than positive. At the same time, the role of the state in forming the prerequisites for the accumulation and growth of human capital is decreasing, since the emphasis of social development has shifted not in favor of the factors of its formation. This is confirmed by the reduction in the share of expenditures for financing all social factors of human development, without exception, in the total amount of state expenditures during the period under study. The key directions and levers for ensuring the sustainable growth of human capital, including during the post-war reconstruction of Ukraine, are proposed, based on the formation of a targeted socio-economic policy aimed at its preservation, accumulation, and development. The levers defined by the authors will make it possible to form a balanced vector of the socio-economic development of society, and their implementation at the state level will contribute to the accumulation, growth, and qualitative transformation of human capital, which, in turn, will create opportunities to increase the level of human development in Ukraine.